Enterprise information systems : 16th International Conference, ICEIS 2014, Lisbon, Portugal, April 27-30, 2014, Revised selected papers /: 16th International Conference, ICEIS 2014, Lisbon, Portugal, April 27-30, 2014, Revised selected papers. (2015) - Unknown
No abstract available